Peculiarities, Results and Consequences of the Repatriation of the Lebanese-Armenians (1946-1949) - Darbinyan, Ofelya (History and Culture, 2021)
In the studies devoted to the Great Repatriation in Armenian historiography, the repatriation of Lebanese-Armenians in 1946-1947, the results and consequences of which simultaneously caused inspiration and disappointment, has not yet been the subject of a separate investigation by any researcher. So far, it has not been the subject of a separate study. This article, giving an importance to the peculiarities of the Lebanese-Armenian community, comprehensively highlights the main shortcomings and omissions that have become an obstacle to the full and effective implementation of the process. The geography of the placement of repatriated Lebanese-Armenians is being clarified. In parallel, the contributions of repatriates to the economy, demography, urban planning and scientific and cultural life of Soviet Armenia are also put forward. The bulletins, letters and publications in a number of archival documents and periodicals, which were gathered up and analyzed, were of primary importance for the research.
Keywords: Diaspora; repatriation; Immigration Committee; Armenian Community of Lebanon; Beirut; Anjar; party; church; AGBU; Soviet Armenia